2020
DOI: 10.1521/soco.2020.38.supp.s1
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five Years of Research Using Implicit Measures

Abstract: The year 2020 marks the 25th anniversary of two seminal publications that have set the foundation for an exponentially growing body of research using implicit measures: Fazio, Jackson, Dunton, and Williams's (1995) work using evaluative priming to measure racial attitudes, and Greenwald and Banaji's (1995) review of implicit social cognition research that served as the basis for the development of the Implicit Association Test (IAT). The current article provides an overview of (1) two conceptual roots that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 126 publications
0
53
0
Order By: Relevance
“…Contrary to our initial expectations, however, we found no evidence, in either study, that extended contact influenced participants' explicit attitudes. Previous research suggests that discordance between implicit and explicit measures is common ( Echabe, 2013 ; Gawronski et al., 2020 ). For example, some studies have found that explicit attitudes can be changed more easily than implicit attitudes ( Gawronski and Strack, 2004 ; Gregg et al., 2006 ; Petty et al., 2006 ), while others have found the opposite ( Barden et al., 2004 ; Dasgupta and Greenwald, 2001 ; Wittenbrink et al., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our initial expectations, however, we found no evidence, in either study, that extended contact influenced participants' explicit attitudes. Previous research suggests that discordance between implicit and explicit measures is common ( Echabe, 2013 ; Gawronski et al., 2020 ). For example, some studies have found that explicit attitudes can be changed more easily than implicit attitudes ( Gawronski and Strack, 2004 ; Gregg et al., 2006 ; Petty et al., 2006 ), while others have found the opposite ( Barden et al., 2004 ; Dasgupta and Greenwald, 2001 ; Wittenbrink et al., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this chapter we have provided a brief, even gentle, introduction to the vast literature on implicit social cognition. For those who wish to immerse themselves more deeply in this work, the recent special issue of Social Cognition marking 25 years of implicit social cognition research (Gawronski, De Houwer, & Sherman, 2020) may serve as a useful starting point. In any case, we do hope that interested readers will come away with explicit recollection of a few basic findings from this enormous and burgeoning field:…”
Section: Seven Takeaways To Remembermentioning
confidence: 99%
“…Indeed, the plethora of indirect measures differ substantially along these dimensions. The only feature that they all share is that they infer evaluations from performance on some task rather than by directly asking respondents to provide them (e.g., Corneille and Hütter, 2020 ; Gawronski et al, 2020 ). That is, they are indirect measures of evaluation.…”
Section: Definitional Issuesmentioning
confidence: 99%